Civil drafting technology - Madsen, David A. (Prentice Hall, 1998)
Ideal for a one-term or semester course, this text provides a broad understanding of civil drafting and a working knowledge of the basic components of mapping. Eleven chapters discuss surveying fundamentals, location and direction, mapping scales, mapping symbols, legal descriptions and plot plans